A waterborne outbreak of multiple diarrhoeagenic Escherichia coli infections associated with drinking water at a school camp. (January 2018) - Park, Jungsun; Kim, Jin Seok; Kim, Soojin; Shin, Eunkyung; Oh, Kyung-Hwan; Kim, Yonghoon; Kim, Cheon Hyeon; Hwang, Min Ah; Jin, Chan Mun; Na, Kyoungin; Lee, Jin; Cho, Enhi; et al.
Highlights: In June 2015, an outbreak of acute gastroenteritis occurred in a school camp. Diarrhoeagenic Escherichia coli strains were isolated from clinical and drinking water samples. The camp used groundwater drawn from a private underground reservoir. The outbreak investigation revealed some problems with the water supply system, such as the use of inappropriate filters in the water purifier and a defect in the pipeline between the reservoir and the chlorination device. The management of drinking water quality in group facilities should be strengthened. Abstract: Background: In June 2015, a local public health laboratory was notified that students had developed gastroenteritis symptoms after attending a camp. An outbreak investigation was conducted to determine the extent and cause of the outbreak. Method: A retrospective cohort study was conducted to determine the correlations between the illness and specific exposures at the school camp. All attendees were interviewed with a standard questionnaire that addressed clinical symptoms, food consumption, and environmental exposures. Clinical specimens were cultured using standard microbiological methods for bacterial and viral pathogens. The genetic relationships of all isolates were determined using pulsed-field gel electrophoresis (PFGE). Results: A total 188 patients with symptoms of diarrhoea, abdominal pain, and nausea were identified. The completed questionnaires suggested that the consumption of drinking water was likely to be linked to this outbreak. Using microbiological methods, enterohaemorrhagic Escherichia coli, enteropathogenic E. coli, and enteroaggregative E. coli were isolated, and the isolates from both patient stool and environmental water samples displayed indistinguishable XbaI -PFGE patterns. The water system in the camp used groundwater drawn from a private underground reservoir for cooking and drinking. The environmental investigation revealed some problems with the water supply system, such as the use of inappropriate filters in the water purifier and a defect in the pipeline between the reservoir and the chlorination device. Conclusions: This outbreak points to the importance of drinking water quality management in group facilities where underground water is used and emphasizes the need for periodic sanitation and inspection to prevent possible waterborne outbreaks.